Effect of washing on performance attributes of fabrics for Basic School Uniforms (International Journal of Scientific Research and Management (IJSRM), 2021)
The determination of the suitability of fabrics for specific end-uses require the subjection of selected fabrics to conditions they would be exposed to during use and care such as washing. Three different brands of fabrics commonly used for Ghanaian Basic School Uniforms and labelled A, B and C were evaluated after washing to suggest suitable fabric(s) to be used to achieve quality in uniforms. Specimens were subjected to three washing cycles and strength, elongation, dimensional stability and colourfastness tested. Data were analyzed using the Predictive Analytical Software for windows version 22. Means of the performance characteristics of the fabrics were determined and hypotheses were tested using analysis of variance at 0.05 alpha level. Washing had effect on the parameters investigated. In all, fabric brand B performed best as throughout the wash cycles, its strength values were above the standard requirements set by the Ghana Standards Authority for uniform fabrics. Since the fabric brand B performed best with the parameters investigated, it is suggested for use as school uniform fabric. However, further studies can be conducted on these same fabrics where other parameters such as absorbency and abrasion resistance can be evaluated.